Inhibitors of cell cycle checkpoint target Wee1 kinase - a patent review (2003-2022) - Yan, Jingxue; Zhuang, Lili; Wang, Yong; Jiang, Yiqing; Tu, Zhenlin; Dong, Chao; Chen, Yadong; Zhu, Yong (Expert opinion on therapeutic patents, 2022)
DNA damage repair in most malignancies with mutation of p53 is more dependent on the G2/M checkpoint. Wee1 kinase is a key regulator of the G2/M checkpoint. If Wee1 is inhibited, it results in cells with unrepaired DNA damage entering mitosis prematurely, leading to mitotic catastrophe and subsequent cell death via the apoptotic program. Therefore, inhibition of Wee1 kinase which overexpressed in several cancer cell lines has emerged as a promising therapy for cancer treatment. This review summarizes for the first time the structures of small-molecule inhibitors of Wee1 reported in patents published from 2003 to 2022 and the recent clinical developments. It also provides perspectives on the challenges and the future directions. We used different methods to search different databases (PubMed, Reaxys, clinicaltrials.gov)for the literature we needed. Although the small-molecule inhibitors of Wee1, Adavosertib, and ZN-C3 have entered the clinical phase II, the clinical toxicity exhibited by Adavosertib remains the subject of greater concern. The use of Wee1 inhibitors as monotherapy or in combination therapy remains the main trend in Wee1 inhibitors at present.